(3GdeMGSHI GdJMdjdjI s (3OQhS hJeGQjfs - (3eGRhf(B, (3eMeO Cejfs; (3SGdej, jGSjfs ((3GdLRGFQ (B: (3GdfTQ GdLGeYj GdLOjO (B2021s, 2021)
(3eaGgje YGeI Mhd GdeMGSjI GdJMdjdjI, JYQjagG hCgOGagG hhXGFagG, cPdc eMGSHI GdehGO eY eaghe GdeNRhfGJ hWQb JbjjegG hcjajI GdLQO GdOGFe dgG, HGdGVGaI Gdi WQjbI GdJcGdja GdcdjI (B( (3GdCbSGe GdeJLGfSI, GdJcGdja GdZjQ GdeHGTQI, hYdGbJgG HMLe GdfTGW ef KGHJI heJZjQI hTHg eJZjQI Ch GdJcGda GdeNJdWI, eY WQjbI GdJMejd GdYbdGfj ddJcGdja GdKGHJI haj GdCNjQ JMOK Yf GdJcGdja GdeYjGQjI CfhGYgG hCgOGagG eY MSGH GdJcdaI GdeYjGQjI(B.s
Keywords: (3eMGSHI JMdjdjIs